‫إدارة‬‫التدفقات‬ ‫النقدية‬ ‫من‬ ‫خلال‬ ‫أدوات‬ ‫السوق‬ ‫النقدية‬ ‫دراسة‬‫حالة‬ ‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ ‫سوق ‬‫أهراس‬ ‫‪-‬‬ - ‬‫يسمينة‫ غنام ‬; حكيمة ‫بلاوي‬‫ ‬ (My University, 2018)
The aim of this study is to examine the problem of the management of the cash flows through the monetary market tools in economic institutions, our sélection was made at the major mills of « Belghith » during the period (2012-2016) , based on the financial statements of( the financial budget, table of results accounts, cash flow table by the direct method, estimated cash budget). The main findings of the study are that there are a set of difficulties related to the management of the cash flows, the most important of which is the absence of effective follow-up of the treasury budget, the failure to observe the accuracy of forecasting cash inflows and outflows, the usefulness of cash flow schedule is only to monitor the various cash inflows and outflows at the treasury level, and can not be used to manage liquidity and make financial decisions related to financing of the dificit and use of surplus, while the other part is linked to the inefficiency of the algerian monetary market through limited tools and financial products available as a result of laws that govern them,however the institution manages cash flows through the tools offered by the monetary market, highlights the important role played by this latter through its effective in managing liquidity and maximizing returns, which led us to propose diversification in the use of monetary market instruments by the institution to finance its deficit and the use of surpluses, which may be of benefit to them in raising their financial revenues and efficient management of their cash flows. ............................................................... تهدف هذه الدراسة إلى دراسة مشكلة إدارة التدفقات النقدية من خلال أدوات السوق النقدية في المؤسسات الاقتصادية، تم اختيارنا في كبرى مصانع «بلغيث» خلال الفترة الفترة (2012-2016) بناءً على البيانات المالية لكل من (الموازنة المالية، جدول حسابات النتائج، التدفق النقدي الجدول بالطريقة المباشرة، الميزانية النقدية المقدرة). ومن أهم النتائج التي توصلت إليها الدراسة وجود مجموعة من الصعوبات المتعلقة بإدارة النقد التدفقات، وأهمها غياب المتابعة الفعالة لموازنة الخزينة، وعدم مراعاة دقة التنبؤ بالتدفقات النقدية الداخلة والخارجة، وفائدة جدول التدفقات النقدية هي فقط لمراقبة التدفقات النقدية الداخلة والخارجة المختلفة على مستوى الخزينة، ولا يمكن استخدامها لإدارة السيولة وتحقيق المعاملات المالية القرارات المتعلقة بتمويل العجز واستخدام الفائض، في حين يرتبط الجزء الآخر بعدم كفاءة السوق النقدية الجزائرية من خلال الأدوات والمنتجات المالية المحدودة المتاحة نتيجة للقوانين الحاكمة منها، ومع ذلك تقوم المؤسسة بإدارة التدفقات النقدية من خلال الأدوات التي يوفرها السوق النقدي، مما يسلط الضوء على الدور المهم الذي تلعبه هذه الأخيرة من خلال فعاليتها في إدارة السيولة وتعظيم العوائد، وهو ما قادنا اقتراح التنويع في استخدام أدوات السوق النقدية من قبل المؤسسة لتمويل عجزها وعجزها استخدام الفوائض مما قد يعود بالنفع عليهم في رفع إيراداتهم المالية وإدارتها بكفاءة تدفقاتهم النقدية.